Analisis Kesalahan Morfologi Penerjemahan Arab–Indonesia pada ChatGPT - Ruhmadi, Abdul; Al Farisi, Mohamad Zaka (Study Program of Arabic Language Teaching, 2023)
The research focuses on analyzing translation errors in Arabic-Indonesian translations generated by Chat GPT in the field of morphology. The study's objectives are to: 1) Determine whether there are translation errors at the morphological level using the Chat GPT translation system and 2) Identify the areas where translation errors occur in morphology. The research utilizes purposive sampling as the data collection method. Qualitative data is analyzed through a literature review using content analysis techniques. The study's findings reveal the presence of translation errors in Arabic-Indonesian translations generated by Chat GPT at the morphological level. The errors identified include: 1) translating passive verbs into active verbs, 2) translating with the addition of morphemes in the target language, 3) translating verbs into nouns, 4) translating nouns into passive verbs, 5) selecting target language vocabulary that deviates from the source language, and 6) translating words that do not require translation.